Visualization of Carotid Doppler in Patients with Ischemic Stroke at Dr. Hasan Sadikin General Hospital Bandung Year 2016-2019 - Olivia Olivia (Universitas Padjadjaran, 2021)
Background: Various pathological changes in both the intra and extracranial arteries that supply the brain can cause disturbance of cerebral blood flow and perfusion leading to cerebral dysfunction. Doppler ultrasound is able to assess these changes. This study was performed to evaluate the anatomical and physiological changes found in the carotid arteries of patients with ischemic stroke using Doppler ultrasound.